2003
DOI: 10.1149/1.1621418
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Energetics, and Thermal Stability of Nitrogen-Vacancy-Related Defects in Nitrogen Doped Silicon

Abstract: The electronic structure, formation energy, and thermal stability of nitrogen-vacancy related complexes in silicon have been investigated using density functional theory and semi-empirical Hartree-Fock calculations. The calculated energies of formation in the ground state showed that VN 2 was not stable, whereas V 2 N 2 when formed from VN 2 was the most stable, followed by N 2 and V 2 N 2 formed from a divacancy. The calculated free energy changes of the considered chemical reactions confirmed the low stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Consequently, the formation of void will be hindered and their density will decrease compared to N-free CZ Si. These results combined with our previous results obtained from molecular mechanics force field calculations (Karoui et al, 2003;Sahtout Karoui et al, 2004) and experimental measurements (Wright etching, STEM, HRTEM, and Oxygen Precipitates Profiler) (Karoui et al, 2004a(Karoui et al, , 2004b confirm that N 2 and V 2 N 2 are much more likely to adsorb O atoms than to trap vacancies thus act as nucleation centers for oxygen precipitation rather than voids. However, N-O complexes might also co-exist in the oxide layer covered walls of the voids in N-doped Si.…”
Section: Nucleation Of Extended Defects and Nitrogen Concentration Mesupporting
confidence: 81%
“…Consequently, the formation of void will be hindered and their density will decrease compared to N-free CZ Si. These results combined with our previous results obtained from molecular mechanics force field calculations (Karoui et al, 2003;Sahtout Karoui et al, 2004) and experimental measurements (Wright etching, STEM, HRTEM, and Oxygen Precipitates Profiler) (Karoui et al, 2004a(Karoui et al, , 2004b confirm that N 2 and V 2 N 2 are much more likely to adsorb O atoms than to trap vacancies thus act as nucleation centers for oxygen precipitation rather than voids. However, N-O complexes might also co-exist in the oxide layer covered walls of the voids in N-doped Si.…”
Section: Nucleation Of Extended Defects and Nitrogen Concentration Mesupporting
confidence: 81%
“…N 2 V 2 or N 2 V 2 ! N 2 V 2 [5,6]. The N 2 V 2 complex has been shown to attract oxygen into stable complexes, indicating the possibility of further oxygen precipitate nucleation based on the N 2 pair.…”
mentioning
confidence: 99%
“…A number of earlier studies on N-doped Si showed that N atoms form defect complexes comprising N atom pairs and vacancies. [9][10][11] These defect complexes are believed to form deep levels and act as carrier traps. 12,13 The results of the present study, hence, suggest that N-related defect complexes may play a major role in surface recombination of photoexcited carriers in c-Si wafers passivated by SiN x layers.…”
Section: Discussionmentioning
confidence: 99%